2021
DOI: 10.1126/sciadv.abd0772
|View full text |Cite
|
Sign up to set email alerts
|

Neuronavigation-guided focused ultrasound for transcranial blood-brain barrier opening and immunostimulation in brain tumors

Abstract: Focused ultrasound (FUS) in the presence of microbubbles can transiently open the blood-brain barrier (BBB) to increase therapeutic agent penetration at the targeted brain site to benefit recurrent glioblastoma (rGBM) treatment. This study is a dose-escalating pilot trial using a device combining neuronavigation and a manually operated frameless FUS system to treat rGBM patients. The safety and feasibility were established, while a dose-dependent BBB-opening effect was observed, which reverted to baseline with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 68 publications
(94 reference statements)
1
85
1
Order By: Relevance
“…For a clinically safe BBBO parameter (0.63 mechanical index (MI)), the immune cell population did not change noticeably; however, at a higher but still safe dosage (0.81 MI, which caused minimal RBC extravasation), noticeable increases in CD4 + and CD8 + TILs were observed. These observations support the possibility of fine tuning the FUS parameters to induce an appropriate anticancer immune response while simultaneously maintaining the treatment safety [74].…”
Section: Bbbo Anticancer Immune Modulationsupporting
confidence: 66%
See 1 more Smart Citation
“…For a clinically safe BBBO parameter (0.63 mechanical index (MI)), the immune cell population did not change noticeably; however, at a higher but still safe dosage (0.81 MI, which caused minimal RBC extravasation), noticeable increases in CD4 + and CD8 + TILs were observed. These observations support the possibility of fine tuning the FUS parameters to induce an appropriate anticancer immune response while simultaneously maintaining the treatment safety [74].…”
Section: Bbbo Anticancer Immune Modulationsupporting
confidence: 66%
“…An advantage of this system is its relatively low integration complexity, with it being feasible to incorporate the FUS apparatus with currently commercially available neuronavigation systems. This also means that the system could deliver treatments even in the outpatient setting, and a recent study found that the overall procedure can be accomplished within half an hour [ 74 ]. However, a major concern is that the guidance relies on perfect ballistic beam projection offered from numerical treatment planning without actual beam deposition.…”
Section: Clinical Translation Of Bbbomentioning
confidence: 99%
“…The non-invasive approaches suggest the usage of chemical modification of drugs such as lipidization [28], substrates for carrier-mediated transcytosis [29], substrates for receptor-mediated transcytosis, virus-mediated bloodbrain barrier delivery [30,31], and exosome-mediated blood-brain barrier delivery [32]. There are also several methods different from the above two approaches: the intranasal delivery route [33], the modulation of the blood-brain barrier permeability by hyperosmotic agents [34], and the use of focused ultrasound [35].…”
Section: Barriers In Brain and Advances In Drug Delivery Across The Blood-brain Barriermentioning
confidence: 99%
“…A recent study evaluated BTB disruption using FUS with adjuvant temozolomide and showed accurate and safe opening in patients for six sonication cycles at the same targeted sites [ 74 ]. Another recent investigation reported feasibility of BBB opening within peri-enhancing regions of the brain in six patients with recurrent GBM, using the NaviFUS system with concomitant Sonovue microbubbles [ 79 ]. This analysis suggests a dose-dependent BBB permeability effect of FUS, based on DCE kinetic parameter analysis (K trans and V e ) [ 79 ].…”
Section: Clinical Impact Of Fus Mediated Bbb/btb Disruptionmentioning
confidence: 99%
“…Another recent investigation reported feasibility of BBB opening within peri-enhancing regions of the brain in six patients with recurrent GBM, using the NaviFUS system with concomitant Sonovue microbubbles [ 79 ]. This analysis suggests a dose-dependent BBB permeability effect of FUS, based on DCE kinetic parameter analysis (K trans and V e ) [ 79 ].…”
Section: Clinical Impact Of Fus Mediated Bbb/btb Disruptionmentioning
confidence: 99%